Gendhing Pepeling: Media Dakwah Melalui Budaya Lokal Masyarakat Jawa - Agik Nur Efendi (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2019)
The submission of Da'wah is not only done through lectures but also can be done through songs or gendhing (in Javanese terms). The submission of Da'wah through songs has been local wisdom of society since the time of Sunan Kalijaga. Currently, Gendhing Papeling by Ki Anom Suroto is included in the Javanese song that has the influence to invite people to worship. This study aims to determine the dimension of religious value in the lyrics of Papeling song. Besides, this research also tries to convey the form of Da'wah in Islam with a nuance of local culture. This research is included in qualitative research with the type of phenomenology. The source of the data in this study was the song of Pepeling by Ki Anom Suroto. The results showed that the Papeling gendhing is a Javanese song that is rich in religious value. This song contains an invitation to carry out religious orders and become the song ' obligatory ' when there is a puppet show of Leather, Campursari, Ludruk, Tayub, and other Javanese culture.